PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ARTICULATE STORYLINE 3 PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Puti Michelle Maryam; Fikhen Tri Wulandari; Atri Waldi; Hasmai Bungsu Ladiva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The teaching of Pancasila Education in elementary schools continues to be largely dependent on textbooks, conventional lecture-based instruction, and simple learning resources, resulting in limited student participation during classroom activities. Although schools have been equipped with facilities that support technology integration, digital learning media are still not widely utilized. In response to this issue, this study aimed to develop an interactive learning medium using Articulate Storyline 3 combined with the Problem Based Learning (PBL) approach for fourth-grade Pancasila Education. The research adopted a Research and Development (R&D) method through the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection focused on examining the product's validity, practicality, and effectiveness. The findings indicated that the developed media achieved an overall validity score of 97.1%, categorized as very valid, consisting of assessments from material experts (98%), media experts (100%), and language experts (93.3%). Practicality testing also produced highly positive results, with teacher responses reaching 93.33% and student responses attaining 95.6%, both classified as very practical. Furthermore, the effectiveness test based on the N-Gain analysis generated an average score of 0.76, placing the media in the effective category. These results demonstrate that the Articulate Storyline 3-based learning media integrated with the PBL model is suitable for use in fourth-grade Pancasila Education learning activities due to its high validity, practicality, and effectiveness.